Prevalence and risk factors associated with HIV-1 infection among people who inject drugs in Dar es Salaam, Tanzania: a sign of successful intervention? - Samuel Lazarus Likindikoki; Elia John Mmbaga; Germana Henry Leyna; Kåre Moen; Neema Makyao; Mucho Mizinduko; Alex Ishungisa Mwijage; Diana Faini; Melkizedeck Thomas Leshabari; Dan Wolf Meyrowitsch (BMC, 2020)
Abstract Background Prevalence of HIV infection among people who inject drugs (PWID) has been reported to be higher than that of the general population. The present study aimed to estimate the prevalence of HIV infection and associated risk factors among PWID in Dar es Salaam, Tanzania, following the introduction of a comprehensive HIV intervention package (CHIP) for PWID in the country in 2014. Methods We conducted an integrated bio-behavioral survey (IBBS) among PWID using respondent-driven sampling (RDS) in Dar es Salaam, Tanzania, between October and December 2017. Data on socio-demographic characteristics and risky behaviors were collected through face-to-face interviews. Blood samples were collected and tested for HIV infection. We accounted for weighting in the analyses, and logistic regression was performed to assess risk factors for HIV infection. Results A total of 611 PWID (94.4% males and 5.6% females) with a median age of 34 years (IQR 29-38) were recruited. The overall prevalence of HIV infection was 8.7% (95% CI 6.5-10.9). The prevalence of HIV infections for males and females were 6.8% (95% CI 4.7-8.9%) and 41.2% (95% CI 23.7-58.6%) respectively. Adjusted weighted logistic regression analysis (WLRA) showed that being a female (aOR 19.1; 95% CI 5.9-61.8), injecting drugs for more than 10 years (aOR = 7.32; 95% CI 2.1-25.5) compared to 1 year or less and being 45 years or older (aOR = 34.22; 95% CI 2.4-489.5) compared to being 25 years or younger were associated with increased odds of HIV infection. Use of a sterile needle at last injection decreased odds of HIV infection (aOR = 0.3; 95% CI 0.1-0.8). Conclusions The present study observed a decline in prevalence of HIV infections among PWID in Dar es Salaam (8.7%) compared to a previous estimate of 15.5% from an IBBS conducted in 2013. Despite the decrease, HIV prevalence remains high among PWID compared to the general population, and women are disproportionally affected. The decline may be possibly attributed to the on-going implementation of CHIP for PWID, highlighting the need for strengthening the existing harm reduction interventions by incorporating access to sterile needle/syringe and addressing the layered risks for women.